Combining political ecology and pragmatist sociology to repoliticise agrifood systems’ transformations at the territorial scale - Lamine, Claire; Palm, Juliano; Tuscano, Martina; Schmitt, Claudia; Jenatton, Morgan; Marsden, Terry (The International Journal of Sociology of Agriculture and Food, 2025)
Recent crises have led to an increased framing of agrifood systems transformations through the lens of food supply at different scales (global, national, territorial), sometimes justifying neo-productivist perspectives, and often at the expense of environmental issues and social justice. In turn, this produced a broader depoliticisation of food systems transformations despite an institutional politicisation, i.e. an increased integration in policy narratives, often with limited real effects. We suggest that pragmatist sociology and political ecology might offer fruitful insights for addressing this issue in a repoliticised way. These two literatures show how people identify problems affecting agri-food systems and collectively work to find solutions while, at the same time, recognising the plurality of understandings of transition pathways and highlighting the mechanisms through which some actors and worldviews are neglected when it comes to defining possible paths of transformation. Inspired by these literatures, we have established three key guiding questions dealing with the processes of definition of the food systems’ transformations as a shared and collective problem, the analysis of the reconfigurations of power relations, and the recognition of the diversity of visions of the food system. These guiding questions, that can orientate both analytical and transformative perspectives, emerged and were tested in three territorial case studies in France and Brazil. They appear useful not only for the scientific analysis of de/repoliticisation processes, primarily because they reveal the contrasted effects of the increasing institutionalisation and legitimisation of agrifood transitions but also for developing a transformative approach allowing to repoliticise this issue.